Evaluation of sub-chronic adverse effects of Dracocephalum kotschyi hydroalcoholic extract on blood biochemical and hematological biomarkers in rats - Hosseini-Sharifabad, Ali; Rahimirigi, Nastaran; Sadraei, Hassan; Yegdaneh, Afsaneh; Talebi, Ardeshir (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: Dracocephalum kotschyi is a medicinal plant native to Iran, which is known for its anti-inflammatory and spasmolytic properties. This study was conducted to investigate the sub-chronic adverse effects of D. kotschyi extract on biochemical and hematological biomarkers in rats, with the aim of identifying any potential adverse effects associated with long-term therapy. Methods: A total of 50 male Wistar rats were randomly allocated into 5 separate groups, each consisting of 10 rats. The extract was administered orally for 90 days at doses of 25, 75, and 300 mg/kg in three distinct groups. A control group and a vehicle-treated group were also included in this study. Following the treatment period, blood samples were collected to assess biochemical and hematological parameters. Liver and kidney tissue samples were prepared for histological examination. Mean comparisons between groups were conducted using the one-way analysis of variance (ANOVA), with P values less than 0.05 considered statistically significant. Results: The hydroalcoholic extract of D. kotschyi at a dose of 300 mg/kg significantly increased levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and creatinine (Cr). Additionally, ALT and alkaline phosphatase (ALP) levels were significantly elevated at the dose of 75 mg/kg. Other parameters, including electrolytes, glucose, lipid profiles, thyroid hormones, complete blood count (CBC), prothrombin time (PT), and international normalized ratio (INR), remained unaffected, and no tissue damage was observed in the histological examinations. Conclusion: Long-term oral administration of D. kotschyi extract at anti-inflammatory doses in rats resulted in no significant changes in the measured plasma biochemical or hematological biomarkers. However, at higher doses, there was an increase in hepatic biomarkers, as well as LDH and Cr levels, indicating potential organ toxicity associated with overdose.